ANALISIS KUALITAS PELAYANAN CUSTOMER SERVICE DALAM PENGURUSAN SURAT KETERANGAN RENCANA KOTA DI UNIT PELAYANAN TERPADU SATU ATAP KOTA SURABAYA - Esti Indah Saraswati (Faculty of Social and Political Science, 2016)
The quality of public services always with the interests of society as a customer, but as long as these connote community service given by the officer UPTSA Surabaya City to the community tend to be less good and not qualified. This study was descriptive qualitative method through observation, interviews and documentation. Informants involved is the Head UPTSA Surabaya, Head of Sub Unit UPTSA, cs officer and the applicant UPTSA SKRK in Surabaya. The results obtained from this study is the 5 dimensions of service quality tangible, reliability, responsiveness, assurance, and empathy in the management of the City Plan Certificate in Integrated Service Unit One Roof Surabaya already relatively suitable but there is still need to be improved.